2017
DOI: 10.1111/apt.13969
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial: faecal microbiota transplantation for recurrent Clostridum difficile infection – fresh, or frozen, or lyophilised microbiota from a small pool of healthy donors delivered by colonoscopy

Abstract: Comparative efficacy in faecal microbiota transplantation was observed in subjects receiving fresh or frozen faecal product from the same donors. The lyophilised product had a slightly lowered efficacy compared with fresh product, but it resembled other treatments in microbial restoration 1 month after faecal microbiota transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
137
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(152 citation statements)
references
References 31 publications
5
137
0
10
Order By: Relevance
“…One double blind, randomised study concluded that enema-administered frozen FMT (n=91) was non-inferior for clinical resolution of diarrhoea to fresh FMT (n=87) for the treatment of recurrent or refractory CDI16 (with frozen FMT in this study stored at −20°C for up to 30 days). A further randomised study demonstrated statistically comparable remission rates for recurrent CDI with fresh or frozen FMT delivered colonoscopically (n=25/25 vs 20/24 respectively, P=0.233) (using frozen FMT stored at −80°C for up to 6 months) 13. These data support the findings of earlier small observational studies 35 41.…”
Section: Rationale For Recommendationssupporting
confidence: 80%
See 3 more Smart Citations
“…One double blind, randomised study concluded that enema-administered frozen FMT (n=91) was non-inferior for clinical resolution of diarrhoea to fresh FMT (n=87) for the treatment of recurrent or refractory CDI16 (with frozen FMT in this study stored at −20°C for up to 30 days). A further randomised study demonstrated statistically comparable remission rates for recurrent CDI with fresh or frozen FMT delivered colonoscopically (n=25/25 vs 20/24 respectively, P=0.233) (using frozen FMT stored at −80°C for up to 6 months) 13. These data support the findings of earlier small observational studies 35 41.…”
Section: Rationale For Recommendationssupporting
confidence: 80%
“…Efficacy is similar whether FMT is fresh or frozen, but modestly reduced when using a lyophilised FMT product 13. Colonoscopic delivery of donor FMT into the ileum or caecum was associated with a 91% cure rate for recurrent CDI 14.…”
Section: Rationale For Recommendationsmentioning
confidence: 97%
See 2 more Smart Citations
“…A recent study comparing lyophilized FMT product with fresh or frozen products (using same donors) revealed lyophilized product had slightly lower efficacy (vs fresh), whereas no difference between fresh and frozen fecal product was identified [410]. The hygiene hypothesis, one of the longest standing theoretical frameworks associated with the pathogenesis of IBD [4, 411414], also happens to underpin the single most unexplored aspects of FMT administration, namely optimum timing for microbiota modulation.…”
Section: Microbiome-therapymentioning
confidence: 99%